RENAL VEIN CAVERNOUS HEMANGIOMA – RESECTION AND GRAFTING WITH INTERNAL JUGULAR VEIN - Galama, Rita (2024)
Cavernous hemangioma of the renal vein is an exceptionally rare condition characterized by the presence of a vascular tumor within the renal vein. Limited information is available regarding its clinical features, prevalence, and treatment options. We present the case of a 67-year-old male with gastric adenocarcinoma who underwent staging imaging revealing an incidental finding of a neoformation within the left renal vein. The patient underwent radical total gastrectomy with excision of the renal vein lesion, followed by reconstruction using the internal jugular vein. Histopathological examination confirmed tubular gastric adenocarcinoma and a cavernous hemangioma involving the renal vein wall. The patient was followed in the medical oncology consultation for gastric cancer. At the 10-month follow-up, the patient remains clinically well, with no evidence of recurrence of either the gastric adenocarcinoma or renal vein hemangioma cavernosum. This case highlights the extremely rare incidental discovery of a renal vein hemangioma cavernosum during gastric cancer staging. Surgical excision with vein reconstruction proved to be a safe and effective treatment option. Further research is needed to establish optimal management strategies for this rare condition.